Study on solutions of heat problems using finite difference methods and method of lines incorporate with RK-liked methods - Wan Abdullah, Wan Rukaida (2004)
This dissertation reports a comparison of results from two classes of numerical methods for heat problems. The heat or diffusion equation, which is an example of parabolic equations are classified into the categories of the partial differential equations. Two classes of numerical methods, Method of Lines and Finite Difference Method are discussed. In Method of Lines, several Runge-Kutta methods were incorporated, including the third and fourth order. Finally, analysis on numerical results for the three heat problems is presented.